Characterizing the adult exposome in men and women from the general population: Results from the EHES-LUX study. (March 2023) - Ruiz-Castell, Maria; Le Coroller, Gwenaëlle; Pexaras, Achilleas; Ciprián, Giovana M.; Fagherazzi, Guy; Bohn, Torsten; Maitre, Léa; Sunyer, Jordi; Appenzeller, Brice M.R.
Abstract: Throughout life individuals are exposed to a large array of diverse environmental exposures (exposome). Hair analyses can assess chronic exposure to a large number of chemicals with less intra-variability than urine and blood. This is essential for studies that aim to achieve a global vision of the exposome. We aimed at characterizing the adult exposome by describing 175 environmental exposures and correlation patterns between and within exposure groups. A subsample of participants of the European Health Examination Survey, covering information on exposure to chemical pollutants in hair samples, were included in the present analysis (N = 442). Concentrations of micronutrients, lifestyle, home environment and socioeconomic information completed the exposome description and were obtained through blood analyses and questionnaires. We detected 29 persistent and non-persistent chemical pollutants in more than 70% of hair samples. Compared to women, men had higher concentrations of pesticides, lower concentrations of micronutrients (with the exception of vitamin A), and presented higher alcohol consumption. Across all exposures, a low median absolute correlation was found, 0.05 (5th − 95th centiles = 0.10, 0.20). We observed higher correlations and median correlations within exposure groups than between groups of exposure. The highest median correlation was observed between plasticizers (bisphenol A and S) in both men (0.50) and women (0.31). A 70% and 95% of cumulative variance was explained by 37 and 73 principal components respectively. We found a wide range of chemical exposures in hair samples of men and women. The adult exposome was complex and multidimensional. Future exposome studies should include hair as a matrix for characterizing exposure to multiple environmental chemicals.